EFFECTIVENESS OF ADMINISTRATIVE SERVICES AT ANANDA BEKASI HOSPITAL CONCERNING THE LEVEL OF PATIENT OR COMMUNITY SATISFACTION - Sudiantini, Dian; Lestari, Puji; Wardhani, Dian Kusuma; Nurhasanah, Shandra Dewi; Theresia, Theresia (LPPM Institut Pendidikan Nusantara Global, 2024)
As a health service institution such as a hospital, its responsibility is to provide services that meet the health needs of the community. Quality service health own roles important in increase health and well-being whole public. The aim of this research is to examine the effectiveness of administrative services at Ananda Bekasi Hospital and its impact on the level of community satisfaction. Through a comprehensive approach, this research evaluates hospital administration processes, including the registration process, patient data management, and communication with patients. Data was collected through interviews and observations to measure public perceptions of administrative services. The method used is by analyzing data to understand the contributing factors to levels satisfaction community as well as recommendations for improvements that can be made by Ananda Bekasi Hospital. Research results indicated that effectiveness service administration at Bekasi City Hospital had an impact positive to levels satisfaction public.